Therapeutic effect of Y-27632 on tumorigenesis and cisplatin-induced peripheral sensory loss through RhoA-NF-κB - Zhu, Yi (Mol Cancer Res, 2019)
Chemotherapy-induced peripheral neuropathy (CIPN) is a major side effect of cancer therapy that frequently requires a reduction or cessation of treatments and negatively impacts the patient’s quality of life. There is currently no effective means to prevent or treat CIPN. In this study, we developed and applied CIPN in an immunocompetent, syngeneic murine Lewis Lung Carcinoma (LLCab) model that enabled the elucidation of both tumor and host responses to cisplatin and treatments of Y-27632, a selective inhibitor of Rho kinase/p160(ROCK). Y-27632 not only preserved cisplatin’s efficacy towards tumor suppression but also the combination treatment inhibited tumor cell proliferation and increased cellular apoptosis. By alleviating the cisplatin induced-loss of epidermal nerve fibers (ENFs), Y-27632 protected tumor-bearing mice from cisplatin-induced reduction of touch sensation. Furthermore, quantitative proteomic analysis revealed the striking cisplatin-induced dysregulation in cellular stress (inflammation, mitochondrial deficiency, DNA repair,etc) associated proteins. Y-27632 was able to reverse the changes of these proteins that are associated with Rho GTPase and NF-κB signaling network, and also decreased cisplatin-induced NF-κB hyperactivation in both foot pad tissues and tumor. Therefore, Y-27632 is an effective adjuvant in tumor suppression and peripheral neuroprotection. These studies highlight the potential of targeting the RhoA-NF-κB axis as a combination therapy to treat CIPN.